2016
DOI: 10.1021/jacs.5b12153
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed, Hydrosilyl-Directed Borylation of Unactivated Alkyl C–H Bonds

Abstract: We report the iridium-catalyzed borylation of primary and secondary alkyl C−H bonds directed by a Si−H group to form alkylboronate esters site selectively. The reactions occur with high selectivity at primary C−H bonds γ to the hydrosilyl group to form primary alkyl bisboronate esters. In the absence of such primary C−H bonds, the borylation occurs selectively at a secondary C−H bond γ to the hydrosilyl group, and these reactions of secondary C−H bonds occur with high diastereoselectivity. The hydrosilyl-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 27 publications
0
39
0
1
Order By: Relevance
“…AC À Ob ond is formed by aT amao-Fleming oxidation, thereby affording a1 ,3-diol as the final product. Thus,1 ,3-diol 174 can be synthesized from alcohol 172,w ith hydrosilane 173 as an intermediate.T he Hartwig group later showed that Ir III catalyst 176 can be applied to silylate [82] or borylate [83] secondary CÀHb onds,a se xemplified by the borylation of the cyclohexyl C À Hbond of hydrosilane 175 to afford boronate 177.T he resulting C À Bb ond can be converted into aC À O, C À N, or C À Cb ond with subsequent reactions.…”
Section: Iridium 2221 Iridium(i)mentioning
confidence: 99%
“…AC À Ob ond is formed by aT amao-Fleming oxidation, thereby affording a1 ,3-diol as the final product. Thus,1 ,3-diol 174 can be synthesized from alcohol 172,w ith hydrosilane 173 as an intermediate.T he Hartwig group later showed that Ir III catalyst 176 can be applied to silylate [82] or borylate [83] secondary CÀHb onds,a se xemplified by the borylation of the cyclohexyl C À Hbond of hydrosilane 175 to afford boronate 177.T he resulting C À Bb ond can be converted into aC À O, C À N, or C À Cb ond with subsequent reactions.…”
Section: Iridium 2221 Iridium(i)mentioning
confidence: 99%
“…[80] ¾hnlich wie bei seinen früheren Arbeiten zur Aktivierung von C(sp 2 )-HBindungen [81] wird zuerst eine Ir I -katalysierte Reaktion angewendet, um den Alkohol zu silylieren und ein Hydrosilan als dirigierende Gruppe einzubauen. Ohne das HydrosilanIntermediat zu isolieren, wird die Silylierung der C-H-Bin- -Katalysator 176 eingesetzt werden kann, um sekundäre C-H-Bindungen zu silylieren [82] oder borylieren, [83] wie durch die Borylierung der Cyclohexyl-C-H-Bindung des Hydrosilans 175 unter Bildung des Boronats 177 demonstriert wurde.Die resultierende C-B-Bindung kann durch nachfolgende Reaktionen in eine C-O-, C-N-oder C-C-Bindung überführt werden. You [87] und Glorius [88] …”
Section: Iridium 2221 Iridium(i)unclassified
“…The development of selective functionalization processes that are able to overcome the reactivity of different C−H bonds represents one of the major challenges of synthetic chemistry . Traditionally, the use of bulky transition‐metal‐based catalysts is a common strategy for selective functionalization of primary and secondary aliphatic C−H bonds . Enzymatic and biomimetic C−H bond oxidation have emerged as new and attractive approaches for C−H bond functionalization because these reactions are very selective and can occur under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Traditionally,t he use of bulky transition-metalbased catalysts is ac ommon strategy for selectivef unctionalization of primary and secondary aliphatic CÀHb onds. [4][5][6][7] Enzy-matic and biomimetic CÀHb ond oxidation have emerged as new and attractive approaches forC ÀHb ond functionalization becauset hese reactions are very selective and can occur under mild conditions. The ability of certain enzymes to catalyze selectiveo xidation is the resulto fi nteractions between the substrate and active site moieties such that site-selective CÀH functionalization is promoted.…”
Section: Introductionmentioning
confidence: 99%